Trends in Sport Sciences: formerly Studies in Physical Culture and Tourism 2015 Vol.22 No.2 - Ogurkowska, Małgorzata; Kawałek, Krzysztof; Zygmańska, Magdalena (Akademia Wychowania Fizycznego w Poznaniu)
Competitive rowing demands long-term, unilateral and non-physiological training. This discipline requires not only technical preparation, but also strength and endurance training, which is largely conducive to the occurrence of micro-traumas that can cumulate and lead to a spectrum of overloading changes in the motor organs, particularly in the lumbar spine. The factor most conducive to the occurrence of pathological changes in the spine is the rowing cycle, both on water and on ergometer, wherein the athlete performs multiple repetitions of maximum flexion and extension in the sagittal plane of the lumbar spine. Of note is the fact that during a single, 90-minute training session the rower engages over 70% of his or her overall muscle mass, performing1800 cycles of flexion and extension. These motions performed with oars as additional weights lead to the overloading of both the active and the passive spine stabilization system. Moreover, the system is impacted by compression forces in excess of 6000 N that can lead to destruction of the motor system. It is therefore necessary to understand the biomechanics of spine movements and to perform the biomechanical analysis of rowing, as well as use conclusions from the analysis in the training process in order to counteract overloading changes in the motor system, particularly the spine
Keywords: lumbar spine; mechanical overload; compression forces